The Effects of Methenolone Enanthate Supplement with Exercise on Rats' Bones - Mehmet Özdemir; Sefa Lök (Selcuk University, 2019)
Abstract It is known that anabolic steroids are used by athletes to increase their performance and cause many health problems. This study aims to analyze the effects of methenolone enanthate supplement with exercise on rats' bones. The study was conducted with 28 28-day-old Wistar male rats obtained from the Chair of the Experimental Medicine Research and Application Center of Selcuk University. The rats were allocated into four groups: C (control, n:6), E (exercise, n:7), M (methenolone enanthate, n:7) and ME (methenolone enanthate+exercise, n:8). The required doses were arranged weekly depending on the rats' live weight for the groups given methenolone enanthate. The rats' front and back extremity bones were dissected, and the humerus and femur bones were dried. Each bone's length, corpus thickness, cortex thickness and medullary diameter points were determined. The results were presented as mean±SD. ANOVA and Duncan's test were used for inter-group comparison of the data. The threshold for statistical significance was p lt;0.05. The femur length was 32.46±0.29 in the C group, 32.60±0.64 in the E group, 31.37±0.50 in the ME group and 31.67±0.52 in the M group. The humerus length was 26.42±0.28 in the C group,26.23±0.59 in the E group, 25.31±0.40 in the ME group and 25.35±0.45 in the M group. The femur and humerus length was statistically significantly shorter in the groups that received methenolone enanthate supplement (M and ME) than that of the other two groups (p lt;0.05). No statistically significant difference was found between the C, E, M and ME groups in terms of the cortex and corpus thickness and medullary diameter of their femur and humerus bones (p gt;0.05). It was concluded based on the study results that methenolone enanthate supplement causes early epiphyseal closure in rats' femur and humerus bones and stops the increase in these bones' length. In addition, exercise was found not to reduce this negative effect of methenolone enanthate. Although the prohibited substances classified as anabolics are considered to increase performance by some athletes, these substances are not recommended for use due to their negative effects on athletes' health.  Keywords: anabolic steroids, methenolone enanthate, rats, femur, humerus